Multiple-input multiple-output fixed wireless radio channel measurements and modeling using dual-polarized antennas at 2.5 GHz. - Erceg, V. (IEEE Transactions on wireless communications)
This paper presents outdoor propagation measurements together with derivative analysis, modeling, and simulation of the 2×2 fixed wireless multiple-input multiple-output (MIMO) channel. Experimental data were collected in the suburban residential areas of San Jose, CA, at 2.48 GHz by using dual-polarized antennas. Measurement results include the estimation of path loss, Rician K-factor, cross-polarization discrimination (CPD), correlation coefficients, and the MIMO channel capacity. An elaborate K-factor model that assumes variation over location, time, and frequency is developed. Distance-dependent CPD models of the variable and constant signal components are proposed. A generalized 2×2 MIMO channel model is then derived based on the correlation among the path loss, the copolarized K-factor, and the CPD's distribution of the constant and scattered signal components. Finally, the MIMO channel response is simulated using the newly developed model, and results are found to be well in agreement with measurements.